Sumas y restas combinadas de polinomios

Ejercicio 4º resuelto

Dados los polinomios:

P(x) = x4 − 2x2 − 6x − 1

Q(x) = x3 − 6x2 + 4

R(x) = 2x4 − 2 x − 2

Calcular:

1P(x) + Q(x) − R(x) =

= (x4 − 2x2 − 6x − 1) + (x3 − 6x2 + 4) − ( 2x4 − 2 x − 2) =

= x4 − 2x2 − 6x − 1 + x3 − 6x2 + 4 − 2x4 + 2x + 2 =

= x4 − 2x4 + x3 − 2x2 − 6x2 − 6x + 2x − 1 + 4 + 2 =

= −x4 + x3 − 8x2 − 4x + 5

2P(x) + 2 Q(x) − R(x) =

= (x4 − 2x2 − 6x − 1) + 2 · (x3 − 6x2 + 4) − (2x4 − 2x − 2) =

= x4 − 2x2 − 6x − 1 + 2x3 − 12x2 + 8 − 2x4 + 2x + 2 =

= x4 − 2x4 + 2x3 − 2x2 − 12x2 − 6x + 2x − 1 + 8 + 2 =

= −x4 + 2x3− 14x2 − 4x + 9

3Q(x) + R(x) − P(x)=

= (x3 − 6x2 + 4) + (2x4 − 2x − 2) − (x4 − 2x2 − 6x − 1) =

= x3 − 6x2 + 4 + 2x4 −2x − 2 − x4 + 2x2 + 6x + 1=

= 2x4 − x4 + x3 − 6x2 + 2x2 −2x + 6x + 4 − 2 + 1=

= x4 + x3 − 4x2 + 4x + 3